Standar Kritik Sastra Arab pada Masa Kontemporer (Perspektif Ahmad Asy-Syāyib dalam Buku Uṣūl Al-Naqd Al-Adabiy) - Nur'aini, Siti; Arsyad, Hafid; Tasnimah, Tatik Maryatut (Universitas Al Azhar Indonesia, 2024)
Contemporary Arab literary criticism has established certain standards of evaluation, significantly differing from the periods of Jahiliyyah to the Umayyad era. This research aims to elucidate the standards of Arab literary criticism in contemporary times, focusing on the book